Accuracy of Lysimeters for Dissolved Copper, Antimony, Lead, and Zinc Sampling under Small Arms Backstop. Issue 8 (25th July 2014) - Martel, Richard; Castellazzi, Pascal; Trépanier, Luc; Laporte-Saumure, Mathieu; Brochu, Sylvie
Abstract : Three assays were conducted to evaluate the reliability of lysimeters in detecting concentrations of Cu, Pb, Sb, and Zn in interstitial water of the vadose zone. Two box lysimeters (BLs) made from polyvinyl chloride (PVC) and polyvinylidene fluoride (PVDF) and three tension lysimeters (TLs) of different types were used. Assays were conducted with two concentrations of dissolved metals, undiluted and diluted in a 1:10 ratio, and at three different pHs. The assays were made to evaluate the sorption induced by the lysimeter material itself, by standard quartz sand added to the BLs, and by two types of glass beads placed around the porous cup of the TLs. Generally, BLs were more suitable for interstitial water sampling than TLs. Among the TLs, the one made of nylon was more reliable than the two others. Box lysimeters are a good choice to obtain accurate and comparable results for Cu, Pb, Sb, and Zn analysis. However, they have to be backfilled with natural soil found at the exact location of the lysimeter and not with standard quartz sand. Nylon TLs can also be used for water sampling for Sb, Pb, and Zn analysis but not for Cu. Glass beads may interact with dissolved metals and their use around the suction cup in TLs can be avoided by using the fine fraction of natural sediments (<125 μm) found at the location of the porous cup. Water samples from TLs do not need to be filtered for dissolved metal analysis because they are already filtered by the porous cup.